(untitled) - Bray, Francesca (New York, N.Y., 1986)
The rice -plant: diversity and intensification ; Paths of technical development ; Water control,...
Keywords: Nông nghiệp,Agriculture; Khía cạnh kinh tế,Economic aspects; Châu Á,Asia